Potential Value of miR-221/222 as Diagnostic, Prognostic, and Therapeutic Biomarkers for Diseases - Song, Jialin; Ouyang, Yuanming; Che, Junyi; Li, Xiaoming; Zhao, Yi; Yang, Kejia; Zhao, Xiaotian; Chen, Yinghui; Fan, Cunyi; Yuan, Weien (Frontiers in Immunology, 2017)
MicroRNAs (miRNAs) are short non-coding RNAs that regulate gene expression by base-pairing with their target messenger RNAs (mRNAs). Dysregulation of miRNAs is involved in the pathological initiation and progression of many human diseases. MiR-221 and miR-222 (miR-221/222) are two highly homologous miRNAs and they are significantly overexpressed in several types of human diseases. Silencing miR-221/222 could represent a promising approach for therapeutic studies. In the present review, we will describe the potential value of miR-221/222 as diagnostic, prognostic and therapeutic biomarkers in a variety of diseases including cancer and inflammatory diseases.